Historical memory in Greece, 1821-1930 - Koulouri, Christina, author.
1 online resource.
Keywords: "This book presents a social and cultural history of collective memory in modern Greece during the first century of state independence, contributing to the debate over the relationship between memory and identity. It discusses how modern Greek society commemorated its distant and recent pasts, both real and imagined, namely Antiquity, Byzantium, the Greek Revolution, and the Asia Minor Catastrophe, how cultural memory was shaped by the various war experiences (victory, defeat, mass death and mourning, refugeedom), and how memory politics became arenas of social and political strife. Historical painting, monuments, historical pageantry, tableaux vivants, national anniversaries, performances of ancient drama and revivals of ancient games are analyzed as instances where the past was visualized, represented, performed and "consumed". An explosion in public history has taken place over the last decades around the world, with a veritable flood of commemorations, anniversaries and "memory wars". As more and more social groups claim the "right to remember", public discourse and polemics have arisen at the same time that traumatic memory has become a field of international academic research. In the arena of public history, historical memory is being constructed through the sentimental, irrational reception of mythological narratives told through images"--